Entrepreneurial tendency of Indonesia remote rural communities: Are the existence of community-based mini-grids matters? - Wibisono, Hafidz; Suryani, Siti; Safina, Shafa Widad (Publisher of Widyagama University of Malang (UWG Press), 2024)
Community-based mini-grids have emerged as a promising solution to deliver electricity to areas where extending the grid is considered too costly. Such mini-grids utilise locally available resources and are managed by the community, offering a more democratic and inclusive decision-making process. However, such systems’ operational and maintenance costs often burden the community, particularly in cases where electricity demand and financial capacity are low. It poses a significant challenge to the sustainability of mini-grid systems in rural areas. While there is an assumption that access to electricity promotes entrepreneurship among rural communities, evidence from studies exploring the roles of electricity in this topic varies. This research contributes to the debates on the nexus of electricity and rural enterprises focusing on people’s entrepreneurial propensity. By interpreting the general entrepreneurial tendency test (GET2) exercised to electricity beneficiaries in remote rural Indonesia, we observed limited evidence on how electricity promotes entrepreneurship among rural communities. Therefore, we argue that people’s propensity to be entrepreneurs needs to be stimulated holistically rather than merely by providing electricity. JEL Classification: L26; O18; R20